2019
DOI: 10.1093/ej/uez013
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Consumption Effects of Transitory Income Shocks*

Abstract: We use the responses of a representative sample of Dutch households to survey questions that ask how much their consumption would change in response to unexpected, transitory income shocks (positive or negative). The questionnaire also distinguishes between relatively small income changes (a one-month increase or drop in income), and relatively larger ones (equal to three-months' income). The results are broadly in line with models of intertemporal choice with precautionary saving, borrowing constraints and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
83
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 36 publications
11
83
3
1
Order By: Relevance
“…The MPC distribution for the LOSS treatment (green histogram) is strongly suggestive of bi-modality-nearly 20% of respondents say that they would fully absorb the loss of $500 by reducing current spending. This sign asymmetry has Figure 4: Spending response to losses also been documented by a relatively recent set of papers (Zafar et al, 2013;Sahm et al, 2015;Bracha and Cooper, 2014;Bunn et al, 2017;Christelis et al, 2017).…”
Section: Lossessupporting
confidence: 62%
See 4 more Smart Citations
“…The MPC distribution for the LOSS treatment (green histogram) is strongly suggestive of bi-modality-nearly 20% of respondents say that they would fully absorb the loss of $500 by reducing current spending. This sign asymmetry has Figure 4: Spending response to losses also been documented by a relatively recent set of papers (Zafar et al, 2013;Sahm et al, 2015;Bracha and Cooper, 2014;Bunn et al, 2017;Christelis et al, 2017).…”
Section: Lossessupporting
confidence: 62%
“…Our average MPC is towards the lower end of the estimates found in the literature, for both hypothetical and actual gains of around this size. However, existing studies, like us, have found that majority of households respond little or not at all in response to an income windfall, but that a small sub-group of households (in our case, around one-fifth) spend a substantial fraction of the income windfall (see, for example, Bunn et al, 2017, andChristelis et al, 2017).…”
Section: Responses To Gainsmentioning
confidence: 51%
See 3 more Smart Citations